LITIGASI DAN NON LITIGASI UNTUK PENYELESAIAN SENGKETA BISNIS DALAM RANGKA PENGEMBANGAN INVESTASI DI INDONESIA (Kajian Penegakan Undang-Undang Nomor 48 Tahun 2009 Tentang Kekuasaan Kehakiman jo Undang-Undang Nomor 30 Tahun 1999 Tentang Arbitrase Dan Altern - Manuasa Saragi (E-Journal Graduate Unpar, 2014)
Business in the frame of investment disputes settlement either litigation or non litigation that giving  legal certainty, utility, and fairness is of  necessary. The research in the dissertation intends to know how Indonesia justice system accommodates business in the frame of investment disputes settlement through litigation and non litigation,  and what kind of regulation of business in the frame of investment disputes settlement through litigation and non litigation that could support  investment developing  in Indonesia to reach Indonesia people welfare.     With the intention of obtaining the answer to the above problem, this research was conducted using the normative legal research method by, among others, using primary and secondary legal sources and interpretation of material in reference to the relevant discipline, analyzing the positive legal enforcement of Legislation Number 48 Year 2009 regarding Judicial Power and Legislation Number 30 Year 1999 regarding Arbitration and the Alternative to Dispute Settlement.  From the analysis and comparison of relevant provision material as well as research of several cases of court verdicts, arbiters’ decisions and any investment agreement, several benefits and weaknesses of one or more litigation are discovered in applying  dispute settlement, such as the loss of momentum caused by time efficiency as the result of very long court procedures. It seems that non-litigation requires strengthening executability, bearing in mind that the concerned parties often show lack of consistency in the deal as the basis of the verdict.The result of research in the dissertation is that the business in the frame of investment disputes settlement through litigation and non-litigation as accommodated in Indonesian legal system have not well carried out as expected. From the selected cases it can be seen that a court verdict is inadequate in meeting all the needs  legal certainty, utility, and fairness in relation to the main needs of the parties in dispute in prioritizing the developing of investment in Indonesia. Still a lot of aspects regarding law enforcement relates especially to business in the frame of investment disputes  need to be improved by the legal professionals that helps investors through litigation and non litigation, and, it is also important to appreciate academic studies (universities) which focusing on the settlement of business disputes in the frame of investment. Later, it is recommended that professional legal practitioners should help to find the solution to dispute settlement or difference of opinions of parties in a partnership relation, should always consistently fulfill partnership contractual relation that consented by parties cooperatively. Key words: litigation, non-litigation